Surface dense discharge from rectangular and trapezoidal channels. (October 2022) - Shacheri, F.; S.R. Nikou, N.; Ziaei, A.N.; Saeedi, M.
Abstract: In this paper, the effect of channel geometry on the characteristics of surface dense jets was experimentally investigated. Their geometric properties for various densimetric Froude numbers were studied for rectangular and trapezoidal channels. A simple innovative image processing technique was implemented to study flow trajectory, jet width, plunge point location, impact point, and location of ultimate discharge mixing zone. For small Froude numbers, F r d ≤ 20, it was observed that the channel geometry was an important parameter influencing the dense flow behavior. The plunge point and impact point for the trapezoidal section were 1.37 and 1.53 times more than the rectangular section, linearly proportional to densimetric Froude number. Longer trajectory in trapezoidal channels leads to better dilution at the impact point. The comparisons showed when the objective was to achieve higher mixing, the trapezoidal section was preferable. However, in terms of the ultimate mixing location, both sections were the same. The closer the shape of the channel to the best hydraulic section (semi-circle section), the geometrical parameters and mixing characteristics would be more appropriate. The non-dimensional equations were determined based on dimensional analysis and regression with R 2  > 0.9 in the rectangular section and R 2  > 0.8 in the trapezoidal section, which are beneficial to design and optimization of marine outfalls on large scales. Highlights: For the small Froude numbers, F r d ≤ 20, it was observed that the channel geometry is an important parameter influencing the behavior of the dense flow. The trapezoidal section provides a longer trajectory, wider jet width, and larger X i . Therefore, it is anticipated that the trapezoidal section will maximize the chance for mixing and entrainment in surface dense discharges, which can reduce environmental hazards via more entertainment. The channel geometry has no influence on the location of the ultimate discharge mixing zone, as this point is enough far from the discharge point. The closer the shape of the channel is to the best form of hydraulic section (semi-circle section), the better will be the geometrical parameters and mixing characteristics of the surface dense discharge channel.